2022
DOI: 10.1111/ele.14151
|View full text |Cite
|
Sign up to set email alerts
|

Predator feeding rates may often be unsaturated under typical prey densities

Abstract: Predator feeding rates (described by their functional response) must saturate at high prey densities. Although thousands of manipulative functional response experiments show feeding rate saturation at high densities under controlled conditions, it remains unclear how saturated feeding rates are at natural prey densities. The general degree of feeding rate saturation has important implications for the processes determining feeding rates and how they respond to changes in prey density. To address this, we linked… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…The rectilinear functional response (H1) may be found if low resource densities are lacking in experiments (Sarnelle and Wilson, 2008), as shown by the orange line and blue dotted-dashed line in (C). The strictly linear functional response (H0) may be found if high, saturating resource densities rarely occur in natural conditions (Coblentz et al, 2022a); see magenta dashed and red lines in (C). The generalized or θ-sigmoid functional response (D) can exhibit differently strong s-shapes controlled by the θ exponent.…”
Section: Introduction 1what Are Functional Responses?mentioning
confidence: 99%
See 1 more Smart Citation
“…The rectilinear functional response (H1) may be found if low resource densities are lacking in experiments (Sarnelle and Wilson, 2008), as shown by the orange line and blue dotted-dashed line in (C). The strictly linear functional response (H0) may be found if high, saturating resource densities rarely occur in natural conditions (Coblentz et al, 2022a); see magenta dashed and red lines in (C). The generalized or θ-sigmoid functional response (D) can exhibit differently strong s-shapes controlled by the θ exponent.…”
Section: Introduction 1what Are Functional Responses?mentioning
confidence: 99%
“…However, Sarnelle and Wilson (2008) suggested that H1 is often an artifact due to the lack of low resource densities in laboratory settings (Figure 1C). Moreover, natural resource densities are frequently narrow, with very high densities missing, leading to unsaturated H0 (Coblentz et al, 2022a; Figure 1C). Real (1977) developed a functional response type allowing for seamless shifting from H2 to H3 (see Figure 1D and Eqns 5/6 in Table 1 for details): the generalized or θ-sigmoid response.…”
Section: Introduction 1what Are Functional Responses?mentioning
confidence: 99%
“…Most relevant work has focused on the gut-evacuation rates of prey mass in fishes, but with little focus on generalist predators' diverse prey attributes (Preston et al, 2017). In the functional-response literature, handling and digestion times are primarily considered important only at high prey abundances, where feeding rates are limited by saturation or satiation (Coblentz et al, 2022;Jeschke et al, 2002). The potential for the effect of which Pearson (1897) warned to alter the interpretation of apparent diets for many more types of taxa indicates that more attention to detection times is warranted, and that factors to which handling and digestion times are sensitive may be more important for feeding rates than currently assumed even at prey abundances far below the point of saturation.…”
Section: Discussionmentioning
confidence: 99%
“…In field settings with lower prey densities, spiders are less likely to capture additional prey during handling and less likely to handle multiple prey at a time, leading to longer handling time estimates. Although some encourage sampling high prey densities to elucidate functional response parameters (Uszko et al, 2020), foraging rates at high densities may be functionally irrelevant in nature (Coblentz et al, 2022). Experimental work may tell us more about interaction strengths in natural communities if experiments focus on realistically low densities.…”
Section: Handling Timementioning
confidence: 99%
“…FoRAGE functional responses paired with prey densities in nature indicate that feeding rates may often be unsaturated in natural settings, functionally corresponding to the Type I form (Coblentz et al, 2022). In Type I responses, foraging is primarily constrained by space clearance rate rather than handling time (DeLong, 2021).…”
Section: Interaction Strengthsmentioning
confidence: 99%